SCIENCE FICTION AND MILITARY ENGLISH: A CASE STUDY IN ITALY AND ROMANIA - Adela CATANĂ (Studia Universitatis Babeş-Bolyai. Philologia)
Science Fiction and Military English: A Case Study in Italy and Romania. Starting from the premise that science fiction arouses the interest of both young adult readers and members of the armed forces, the current paper aims to evaluate the possibility of using this genre as a means of teaching Military English to first-year cadets. Additionally, this is an attempt to fill a gap left by specialized literature at national and international levels. The paper combines an eclectic theoretical framework, a synthesized lesson plan used to design and deliver experimental seminars involving forty cadets from two countries (Italy and Romania) and a survey accompanied by charts and explanations. The lesson plan is largely based on “Rome, Sweet Rome,” a 2011 SF short story by military historian James Erwin, and demonstrates that science fiction – particularly military science fiction—can be an alternative solution to traditional textbooks. The collected data prove that SF sources can help teachers conceive instructive and entertaining language classes, while also providing students with a formal, but comfortable environment, meant to facilitate their acquisition of military terminology and specific knowledge according to the STANAG 6001 requirements. The conclusion emphasises the great potential of the proposed method, but also signals that its successful implementation is heavily dependent on the teacher’s training, commitment and creativity as well as on the students’ receptivity.